Interfering Factors in the Assay of Plasminogen Activators by the Fibrin Plate Method - Wijngaards, G (Thrombosis and Haemostasis, 1979)
The assay of plasminogen activator activities on fibrin plates was re-evaluated with special reference to fibrinolysis inhibitors present in samples and in fibrin plates. The nature, action and stability of inhibiting material were studied in tissues with considerable differences in activator and inhibitor contents! human lung, liver and placenta. Extracts were tested for inhibitory capacity against purified human uterine tissue plasminogen activator, urokinase and plasmin on fibrin plates prepared from different grades of fibrinogens and fibrin.The tissue extracts inhibited fibrinolysis on fibrin plates to varying degrees, dependent on the sample medium, the type of fibrin plate and the kind of plasminogen activator. The influence of inhibitors in the sample and in the fibrin plate was partly abolished by the presence of 2 M KSCN in the sample. The procedure for preparing the samples as described by Astrup and Albrechtsen did not completely eliminate the inhibitory action against the added plasminogen activators.Comparison of urokinase inhibition with tissue activator inhibition by the tissue extracts as to the degree of denaturation in the Astrup and Albrechtsen procedure showed that they have much in common. Nevertheless, some differences were found which indicated the possible existence of separate urokinase and tissue activator inhibitors or of different inhibition mechanisms for these plasminogen activators.